1982
DOI: 10.1021/i200017a005
|View full text |Cite
|
Sign up to set email alerts
|

Fischer-Tropsch synthesis in the slurry phase on manganese/iron catalysts

Abstract: Fischer-Tropsch (FT) synthesis was studied on a specially prepared /Fe catalyst in the slurry phase. Compared to classical K promoted Fe precipitation catalysts, the /Fe catalyst gives higher yields of C2 to C4 olefins, i.e., about 60 g/Nm3 synthesis gas converted. The product slate follows the Schulz-Flory distribution and is little influenced by operational conditions. From the experimental conversion data, rate constants for overall synthesis gas conversion were calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

1982
1982
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 7 publications
(12 reference statements)
0
25
0
1
Order By: Relevance
“…As in the present study the measured data are evaluated on the basis of appropriate slurry reactor models and the hydrodynamic and mass transfer properties can be estimated with sufficient accuracy from previous investigations (Deckwer et al, 1980(Deckwer et al, , 1981(Deckwer et al, , 1982a, it is thought that a more reasonable measure to characterize activity and reproducibility is the first order rate constant evaluated from the experimental data. However, all these quantities also depend on specific operating conditions and hydrodynamic and mass transfer properties, as well.…”
Section: Data Reproducibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As in the present study the measured data are evaluated on the basis of appropriate slurry reactor models and the hydrodynamic and mass transfer properties can be estimated with sufficient accuracy from previous investigations (Deckwer et al, 1980(Deckwer et al, , 1981(Deckwer et al, , 1982a, it is thought that a more reasonable measure to characterize activity and reproducibility is the first order rate constant evaluated from the experimental data. However, all these quantities also depend on specific operating conditions and hydrodynamic and mass transfer properties, as well.…”
Section: Data Reproducibilitymentioning
confidence: 99%
“…However, these studies are mainly based on few data points from the RheinpreuBen-Koppers demonstration plant (Kolbel and Ralek, 1980) operated over 30 years ago. Deckwer et al (1982a) studied the FTS on a Mn/Fe catalyst in a bubble column slurry reactor (BCSR) and the experimental results were analysed from the reaction engineering point of view. The earlier work was reviewed by Kolbel and Ralek ( 1980).…”
mentioning
confidence: 99%
“…This observation combined with chemisorption results suggests that the high olefin to paraffin ratios observed for MnO-supported systems are due to metal-support interaction whose effect is limited to reducing the hydrogenation activity of the catalyst. Manganese oxide-containing iron catalysts, which are known for high selectivity to short-chain olefins, have also been found to follow Schulz-Flory distribution by Deckwer et al (1982). They have concluded that the higher yield of Cz to C4 hydrocarbons in Mn/Fe systems is due to the lower value of chain growth probability.…”
Section: ' C L H H Fmentioning
confidence: 99%
“…Desired compositions of copper-promoted iron-based catalysts were prepared by continuous co-precipitation, using an apparatus and a technique similar to that employed by previous investigators (Kolbel and Ralek, 1980;Deckwer et al, 1982). Unlike conventional batch precipitation, this approach ensures that precipitation occurs at a constant, rather than continuously changing, pH, resulting in much more uniform and predictable particle size and porelstructure.…”
Section: Co -Precipitation Proceduresmentioning
confidence: 99%